Educational Regulation Of Parental Emotions For Children With Special Needs According To Islam - Noornajihan Ja‘afar; Nurul Asiah Fasehah Muhamad; Rezki Perdani Sawai; Joki Perdani Sawai (TARBIYAH FACULTY OF UNU SUNAN GIRI BOJONEGORO, INDONESIA, 2024)
Non-Indexed Publication